Pengaruh Pelatihan Dan Pengembangan Karir Terhadap Kinerja Karyawan Pada Dealer Antar Putra Cimareme - Tiara Sari, Putri; Jaelani, Dede (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
In the ever-evolving business world, employee performance is an important factor in determining the success of a company, including motorcycle dealers. In addition to functioning as dealers, motorcycle dealers also act as customer service centers that have a major impact on customer satisfaction. Training and development are important methods in almost every company because they can improve performance. This study aims to examine the effect of training and development on employee performance at the Antar Putra Cimareme Dealer. The method used is quantitative with multiple linear regression analysis on a sample of 35 people. The results of the study showed that in the partial test (t-test), the t-count value for training (2.374)> t table (1.692) and significance (0.024) <0.05, which means that training has a positive and significant effect on employee performance. For career development, the t-count value (2.483)> t table (1.692) and significance (0.018) <0.05, which indicates a positive and significant effect on employee performance. Overall, training and career development have proven to have a positive and significant effect on employee performance.